Lewis Acidities of Indol‐3‐ylmethylium Ions and Intrinsic Barriers of Their Reactions with Phosphines and Pyridines. Issue 23 (25th July 2016) - Follet, Elsa; Mayer, Peter; Mayr, Herbert
Abstract : Rate and equilibrium constants for the reactions of indol‐3‐ylmethylium ions with triarylphosphines and pyridines were measured spectrophotometrically. The resulting Lewis acid‐base adducts were characterized by NMR and X‐ray crystallography. All rate constants, except those for the reactions of sterically hindered bis(indol‐3‐yl)methylium ion1j with phosphines, agreed within a factor of 4 with those calculated by the correlation log k 20 °C = s N ( N + E ) from previously reported electrophilicity parameters E for indol‐3‐ylmethylium ions and N and s N parameters for phosphines and pyridines. Lewis acidities ( LA ) of indol‐3‐ylmethylium ions were calculated from the correlation log K 20 °C = LA + LB using the benzhydrylium‐based Lewis basicities ( LB ) of phosphines and pyridines and the equilibrium constants for the reactions of these Lewis bases with indol‐3‐ylmethylium ions. The agreement of LA values derived from equilibrium constants of their reactions with different types of Lewis bases shows that indol‐3‐ylmethylium ions have a steric demand similar to the p ‐ and m ‐substituted benzhydrylium ions. For some reactions of indol‐3‐ylmethylium ions with phosphines and pyridines, rate and equilibrium constants could be determined, which allowed us to calculate the Marcus intrinsic barriers and compare them with those for analogous reactions with the dicarbonyl(η 5 ‐cyclopentadienyl)‐(η 2 ‐ethene)iron cation. Abstract : Equilibrium and rate constants for the reactions of aryl(indol‐3‐yl)methylium and bis(indol‐3‐yl)methylium tetrafluoroborates with phosphines and pyridines were measured to determine the Lewis acidities ( LA ) of the carbenium ions and the intrinsic barriers of their reactions with these nucleophiles. Electronic and steric effects of differently substituted indol‐3‐ylium groups are thus quantified.